2022
DOI: 10.1038/s41467-022-34365-8
|View full text |Cite
|
Sign up to set email alerts
|

Capture at the ER-mitochondrial contacts licenses IP3 receptors to stimulate local Ca2+ transfer and oxidative metabolism

Abstract: Endoplasmic reticulum-mitochondria contacts (ERMCs) are restructured in response to changes in cell state. While this restructuring has been implicated as a cause or consequence of pathology in numerous systems, the underlying molecular dynamics are poorly understood. Here, we show means to visualize the capture of motile IP3 receptors (IP3Rs) at ERMCs and document the immediate consequences for calcium signaling and metabolism. IP3Rs are of particular interest because their presence provides a scaffold for ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…The reduction of both proteins could exacerbate the phenotype of mitochondrial Ca 2+ -overload. By evaluating oligomeric dynamic changes using SEC, we found that the OMM channel, VDAC, and MCU's gating regulator, MICU1, showed a matching elution pattern with MCU, and the treatment of Fe 2+ shifted all 3 proteins to the similar earlier fractions of higher order oligomers, which coincided with the elution peak of MIC60, a core structural protein at the crista junctions and contact sites (Zerbes et al, 2012), and IP3R1, the major ER Ca 2+ -channel that delivers Ca 2+ to the OMM (Katona et al, 2022) (Figure 5A, C). These data are consistent with VDAC, MICU1, and MCU being associated in the same super-complexes and suggest a possible spatial reorganization of the MCU super-complexes upon iron elevation, thus allowing easier access to ER Ca 2+ supply.…”
Section: Iron Promotes the Assembly Of Mcu Oligomersmentioning
confidence: 73%
“…The reduction of both proteins could exacerbate the phenotype of mitochondrial Ca 2+ -overload. By evaluating oligomeric dynamic changes using SEC, we found that the OMM channel, VDAC, and MCU's gating regulator, MICU1, showed a matching elution pattern with MCU, and the treatment of Fe 2+ shifted all 3 proteins to the similar earlier fractions of higher order oligomers, which coincided with the elution peak of MIC60, a core structural protein at the crista junctions and contact sites (Zerbes et al, 2012), and IP3R1, the major ER Ca 2+ -channel that delivers Ca 2+ to the OMM (Katona et al, 2022) (Figure 5A, C). These data are consistent with VDAC, MICU1, and MCU being associated in the same super-complexes and suggest a possible spatial reorganization of the MCU super-complexes upon iron elevation, thus allowing easier access to ER Ca 2+ supply.…”
Section: Iron Promotes the Assembly Of Mcu Oligomersmentioning
confidence: 73%
“…Given that calcium homeostasis and signaling is one of the key functional roles of the ER, heterogeneous transport could thus provide an important link between physical structure and biological function. Furthermore, it would be interesting to explore whether contacts between the peripheral ER and other cellular structures, such as mitochondria, tend to preferentially occur at highly connected regions, which may facilitate the delivery of lipids or ions across these contacts (71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the dogma that the IP 3 R-GRP75-VDAC tripartite complex forms a funnel through which Ca 2+ is exchanged from the ER to the mitochondria, requires closer scrutiny. Firstly, there is evidence that other binding partners can interact with IP 3 R to form ERMCS where Ca 2+ exchange occurs, as is the case for IP 3 R interacting with the AKAP1 transmembrane domain or TOM70 on the mitochondrial membrane (Katona et al, 2022). Although it is important to note that TOM70 has been shown to interact directly with the IP 3 R-GRP75-VDAC complex (SECTION 3.3); therefore, TOM70 may well be a coincident reporter of the same IP 3 R-GRP75-VDAC junctions.…”
Section: Perspectives and Concluding Remarksmentioning
confidence: 99%
“…Recent evidence suggests that IP 3 Rs may play a structural role in ERMCS formation which is independent of their ability to deliver Ca 2+ from the ER for mitochondrial uptake via the MCU. HEK293 cells are reported to show limited ER–mitochondrial Ca 2+ transfer, but tight IP 3 R-dependent ERMCS (Katona et al, 2022). HEK293 cells lacking IP 3 R showed fewer regions of close apposition (<20 nm) between the ER and mitochondria and re-expression of IP 3 Rs including a non-Ca 2+ conducting mutant in HEK293 cells rescued the contacts between the ER and mitochondria (Katona et al, 2022).…”
Section: Localisation and Functioning Of Ip3rs At Ermcsmentioning
confidence: 99%
See 1 more Smart Citation